Awareness and knowledge of uterine fibroid among women in Kerala, India - Neelima Venugopal; Nissy Jacob; Venkateswaramurthy Nallasamy; Sambathkumar Ramanathan (Intelektual Pustaka Media Utama, 2022)
Uterine fibroid is a common pelvic tumor seen in women of reproductive age causing complications and affecting the quality of life of women. Despite the fact that fibroids are ubiquitous and have a major impact, public awareness of uterine fibroids is exceedingly low. Hence, the study aims to determine the amount of awareness present about uterine fibroid among women in Kerala. In order to assess the knowledge, an online based survey was carried out among women (n=417) for a period of six months. For that we had prepared a questionnaire which was divided into 2 parts, part 1 contains sociodemographic details of the participants, while the next part consisted of 21 questions which evaluates the knowledge of women towards uterine fibroid. The contact numbers or mail ID of women of different age groups were collected from certain women’s social groups and the prepared questionnaire has been sent to women through social medias such as WhatsApp, Facebook, Gmail and the responses were collected. This study concluded that, approximately 66.4% of women are aware of uterine fibroid, while the rest have various misconceptions, and thus awareness must be spread about it. Various measures such as educational programs and camps must be conducted in rural areas to improve the awareness of uterine fibroid among women which help in early management and thereby preventing the complications of the disease.